Pengembangan Microcontroller Embedded System untuk Training Kits - Yoyo Somantri (ELECTRANS, 2016)
this paper describes the results of microcontroller training kit without personal computers (PC) in the programming process.  This device is more effective and efficient to apply and have the same performance if the user to program the microcontroller using a PC. Distance measuring sensors added to this device, as an increased feature. This device is used as a training or learning media microcontroller, equipped with component I/O: keypad, push button, LED, seven segment displays, LCDs, stepper motors and sensors. Experiments carried out by conducting trial's addition of a proximity sensor on the input. This training kit can function according to design specifications, and performed well as a range discoverer.